Atmosphere Monitoring System in Chemistry Laboratory using WSN - Sneha C. Pawar; Dr.J. S. Awati (Journal of Electronic Design Engineering, 2018)
The impact of air quality has to be taken into consideration especially when dealing with different chemical gases in an enclosed Chemistry Laboratory. Thus the monitoring of the environment or the air quality in the Chemistry Laboratory is essential to detect the amount of concentration of gases in the air so as to develop appropriate strategies to reduce the adverse effect of air quality on the health of people working in the laboratory. The Environment Monitoring System is designed using the Wireless Sensor Network technology. Wireless Sensor Network along with Internet of Things allows the use of various sensors to detect the environmental condition and to collect the sensor data thus permitting data integration. The system designed to monitor the environmental conditions in the Chemistry Laboratory is divided into three parts:1] Sensor node: That collects and transmits the sensor data to the central repository or the Sink node 2] Sink node: It is the core node in the network performing important functions like data storage, data collaboration, computing and data integration 3] Web Interface: Development of a Web application so as to provide access to the remote user to the sensor data and also for visualization of data in a systematic manner for further analysis. The system consists of sensor nodes designed using the Atmega328 microcontroller along with a nRF24l01 module for wireless communication and various analog sensors. The base station is designed by using the open source hardware Raspberry Pi, nRF24l01 module and analog sensors. A Web Server Interface is created to access the sensor data for the user.